Educational curricula and the intellectual security industry: a theoretical and analytical study - Hayat BOUBALOUTA; Djida ARIFI (Social Sciences Journal, 1970)
Intellectual security is a fundamental element in the stability and cohesion of societies, as it aims to guide individuals' thoughts toward a balanced path that reinforces positive values and protects against ideological deviations. Educational curricula are among the most essential tools for achieving this goal, as they not only transmit knowledge but also contribute to shaping awareness, enhancing critical thinking, fostering cultural identity, and building conscious generations capable of confronting extremist ideas with awareness and understanding.This study aims to highlight how educational curricula contribute to achieving intellectual security by providing a theoretical perspective on both variables and emphasizing this role. The findings confirm that educational curricula have a clear and significant impact on intellectual security, provided they are utilized appropriately.